2000
DOI: 10.1177/000313480006600107
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Cholecystostomy is an Effective Treatment for High-Risk Patients with Acute Cholecystitis

Abstract: We sought to determine the safety, efficacy, and outcome of percutaneous cholecystostomy (PC) in all patients undergoing the procedure at our institutions. We reviewed 53 consecutive cases of acute cholecystitis seen at our hospitals over 5.5 years in which PC was performed at the initial treatment. Follow-up was obtained by chart review and telephone questionnaire. Acute cholecystitis was the primary admitting diagnosis in 18 cases. In the remaining 35, cholecystitis developed during hospitalization. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Percutaneous drainage of the gallbladder has been developed as a less invasive procedure compared to open cholecystectomy in critically ill patients with AC. From a technical point of view, it is a rather uncomplicated procedure with a low complication rate that is reported to range from 3 to 13% [7–21, 32, 33]. The complication rate in this current series was 8.7% with no major complication.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Percutaneous drainage of the gallbladder has been developed as a less invasive procedure compared to open cholecystectomy in critically ill patients with AC. From a technical point of view, it is a rather uncomplicated procedure with a low complication rate that is reported to range from 3 to 13% [7–21, 32, 33]. The complication rate in this current series was 8.7% with no major complication.…”
Section: Discussionmentioning
confidence: 56%
“…Since first reported in 1980 [6], several series have demonstrated the feasibility of PD in high-risk patients with AC-related sepsis [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. However, there are only scarce data comparing PD to emergency surgery, i.e., laparoscopic cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%
“…[8] PC has been a successful and effective treatment option in patients who cannot undergo LC due to comorbid diseases and do not respond to conservative treatment. [9][10][11] , they reported that 32 of 45 patients achieved recovery with PA at once. Success was achieved in 11 of the remaining 13 patients following the second application of PA.…”
Section: Discussionmentioning
confidence: 99%
“…In the study reported by Yao et al, all patients undergoing PTC demonstrated clinical improvement within 3 days; this improvement helped these patients transition to surgery with acceptable risks [6]. However, the reported rates of acute cholecystitis recurrence after cholecystostomy in patients with gallstones may range from 25% to 30% [30]. It has been shown in the literature that PTC typically leads to multiple readmissions, extended hospital stays and higher hospital costs [31].…”
Section: Surgical Indicationsmentioning
confidence: 99%